Acute toxicity of triazophos and its effects on biochemical parameters in buffalo calves - SANDHU, H S; BAL, M S (The Indian Journal of Animal Sciences, 2013)
Single oral administrations of 1.0. 2.5 and 5.0 mg/kg body weight of triazophos produced mild to moderate toxic symptoms of anticholinesterase poisoning in buffalo calves. The lowest dose was not lethal. whereas 2.5 and 5.0 mg/kg produced 50 and 100 % leathality within 32-120 and 6.5-31 hr after dosing respectively. Triazophos in different doses inhibited erythrocyte cholinesterase (50.3 - 82.4%) and plasma carboxylesterase (37.4 - 54.5%). The inhibition of erythrocyte cholinesterase was dose-dependent and correlated well with severity of toxicity. There was marked elevation in the plasma levels of total proteins and blood urea nitrogen, following triazophos intoxication.